2014
DOI: 10.1371/journal.pone.0100883
|View full text |Cite
|
Sign up to set email alerts
|

A GPBAR1 (TGR5) Small Molecule Agonist Shows Specific Inhibitory Effects on Myeloid Cell Activation In Vitro and Reduces Experimental Autoimmune Encephalitis (EAE) In Vivo

Abstract: GPBAR1 is a G protein-coupled receptor that is activated by certain bile acids and plays an important role in the regulation of bile acid synthesis, lipid metabolism, and energy homeostasis. Recent evidence suggests that GPBAR1 may also have important effects in reducing the inflammatory response through its expression on monocytes and macrophages. To further understand the role of GPBAR1 in inflammation, we generated a novel, selective, proprietary GPBAR1 agonist and tested its effectiveness at reducing monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 32 publications
8
44
1
Order By: Relevance
“…Recently, a small molecule agonist of the bile acids receptor GPBAR1/TGR5 has exerted the same anti‐inflammatory effect on myeloid cell activation in vitro (Lewis et al, ) as shown by other agonists like TUDCA (Yanguas‐CasĂĄs et al, ) and betulinic acid (McMillin et al, ) on microglia. Mice treated with that TGR5 agonist showed reduced monocyte and microglial activation and reduced trafficking of monocytes and T cells into the CNS, correlating with a reduced clinical score in an animal model of experimental autoimmune encephalomyelitis (EAE, Lewis et al, ). We believe that TUDCA might have the same effect as this GPBAR1/TGR5 agonist, inhibiting by itself both the activation of microglia and the infiltration of blood monocytes into the neural parenchyma (Yanguas‐CasĂĄs et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…Recently, a small molecule agonist of the bile acids receptor GPBAR1/TGR5 has exerted the same anti‐inflammatory effect on myeloid cell activation in vitro (Lewis et al, ) as shown by other agonists like TUDCA (Yanguas‐CasĂĄs et al, ) and betulinic acid (McMillin et al, ) on microglia. Mice treated with that TGR5 agonist showed reduced monocyte and microglial activation and reduced trafficking of monocytes and T cells into the CNS, correlating with a reduced clinical score in an animal model of experimental autoimmune encephalomyelitis (EAE, Lewis et al, ). We believe that TUDCA might have the same effect as this GPBAR1/TGR5 agonist, inhibiting by itself both the activation of microglia and the infiltration of blood monocytes into the neural parenchyma (Yanguas‐CasĂĄs et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…More recently, the use of agonists for bile acid receptors has been proposed for the management of multiple sclerosis, as bile acid signaling can modulate inflammation. Indeed, Lewis et al (79) developed a novel agonist for TGR5 that reduces proinflammatory cytokine production from mouse monocytes stimulated with LPS, and this therapeutic was found to reduce EAE severity in mice. FXR also seems to play a role in the progression of EAE, as mice with genetic knockout of FXR have a more severe grade of EAE compared to wild-type EAE mice (80).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Furthermore, rs11554825, a TGR5 single-nucleotide polymorphism, is associated with primary sclerosing cholangitis and ulcerative colitis development, and homozygous individuals for the G allele of rs3731859 which is in perfect linkage disequilibrium (LD) with the risk allele C of rs11554825 demonstrate low TGR5 expression levels, suggesting TGR5 may be important in the development of primary sclerosing cholangitis and ulcerative colitis pathogenesis [35]. In the multiple sclerosis animal model, experimental autoimmune encephalomyelitis (EAE) mice, TGR5 agonist resulted in decreased activation of monocyte and microglial activation, decreased trafficking of monocytes and T cells into the central nervous system (CNS), and improvement of EAE clinical scores, suggesting TGR5 may be a potential therapeutic target in multiple sclerosis [16].…”
Section: ) Tgr5mentioning
confidence: 99%
“…Recently, bile acids were found to regulate inflammation and mediate immune homeostasis [9][10][11][12][13][14][15][16]. Moreover, natural, semi-synthetic, and fully synthetic drugs that target these receptors were developed and are currently being studied for use in various inflammatory disorders such as alcoholic hepatitis, non-alcoholic steatohepatitis, primary biliary cirrhosis, primary sclerosing cholangitis [17,18].…”
Section: Introductionmentioning
confidence: 99%